HIGH VOLUME BRICK POWDER CONCRETE SYNERGISTIC WITH METAKAOLIN: PHYSICOMECHANICAL PROPERTIES AND DRYING SHRINKAGE - Mahmood Fawzi Ahmed (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Currently, sustainability of the construction and building industry taken a priority. This study investigates the feasibility of using a high volume (up to 50%) of blended waste brick powder (BP) and metakaolin (MK) as ordinary Portland cement (OPC) replacements. The binder of the control mixture was a blend of 50% OPC and 50% BP, while the other two mixes were prepared by substituting 10% and 20% of BP with MK. The characteristics of fresh concrete were assessed depending on measuring the mixture temperature, the fresh density, and the workability. The bulk density, and the mechanical properties were investigated and tested at 7 and 28 days. In the line of durability parameters, the void content and drying shrinkage up to 90 days of all mixtures were evaluated. The findings have demonstrated that the control mixture achieved high workability (slump =180 mm), structural compressive strength (34 MPa) at 28 days, low void content (<3%), and acceptable shrinkage strain. The workability of the mixes containing 10%MK:40%BP and 20%MK:30%BP has slightly decreased, while the mechanical properties were increased and the drying shrinkage were declined. However, the inclusion of This study highlighted an ecological technique toward waste management of construction materials and confirmed the possibility of including a high volume of BP as a cementitious material to synthesize more sustainable concrete.